The DKTK EXLIQUID consortium - exploiting liquid biopsies to advance cancer precision medicine for molecular tumor board patients - Mack, Matthias; Janning, Melanie; Loges, Sonja; Sültmann, Holger (Journal of laboratory medicine, 2022)
Testing for genetic alterations in tumor tissue allows clinicians to identify patients who most likely will benefit from molecular targeted treatment. EXLIQUID - exploiting liquid biopsies to advance cancer precision medicine - investigates the potential of additional non-invasive tools for guiding therapy decisions and monitoring of advanced cancer patients. The term “liquid biopsy” (LB) refers to non-invasive analysis of tumor-derived circulating material such as cell-free DNA in blood samples from cancer patients. Although recent technological advances allow sensitive and specific detection of LB biomarkers, only few LB assays have entered clinical routine to date. EXLIQUID is a German Cancer Consortium (DKTK)-wide joint funding project that aims at establishing LBs as a minimally-invasive tool to analyze molecular changes in circulating tumor DNA (ctDNA). Here, we present the structure, clinical aim, and methodical approach of the new DKTK EXLIQUID consortium. Within EXLIQUID, we will set up a multicenter repository of high-quality LB samples from patients participating in DKTK MASTER and local molecular tumor boards, which use molecular profiles of tumor tissues to guide targeted therapies. We will develop LB assays for monitoring of therapy efficacy by the analysis of tumor mutant variants and tumor-specific DNA methylation patterns in ctDNA from these patients. By bringing together LB experts from all DKTK partner sites and exploiting the diversity of their particular expertise, complementary skills and technologies, the EXLIQUID consortium addresses the challenges of translating LBs into the clinic. The DKTK structure provides EXLIQUID a unique position for the identification of liquid biomarkers even in less common tumor types, thereby extending the group of patients benefitting from non-invasive LB testing. Besides its scientific aims, EXLIQUID is building a valuable precision oncology cohort and LB platform which will be available for future collaborative research studies within the DKTK and beyond.